Mutation and association analyses of the candidate genes ESR1, ESR2, MAX, PCNA, and KAT2A in patients with unexplained MSH2-deficient tumors - Rahner, Nils; Kloor, Matthias (Familial cancer, 2012)
Lynch syndrome (Hereditary non-polyposis colorectal cancer/HNPCC) is a cancer susceptibility syndrome which is caused by germline mutations in DNA mismatch repair (MMR) genes, in particular MLH1 and MSH2. A pathogenic germline mutation in the respective MMR gene is suggested by the finding of a loss of a mismatch repair protein in tumor tissue on immunohistochemical staining combined with an early age of onset and/or the familial occurrence of colorectal cancer. Pathogenic germline mutations are identifiable in around 60% of patients suspected of Lynch syndrome, depending on the familial occurrence. The aim of the present study was to identify novel susceptibility genes for Lynch syndrome. 64 Healthy controls and 64 Lynch syndrome patients with no pathogenic MSH2 mutation but a loss of MSH2 expression in their tumor tissue were screened for rare and disease causing germline mutations in the functional candidate genes ESR1, ESR2, MAX, PCNA, and KAT2A. Thirty variants were identified, and these were then genotyped in an independent sample of 36 mutation negative Lynch syndrome patients and 234 controls. Since a trend towards association was observed for KAT2A, an additional set of 21 tagging SNPs was analyzed at this locus in a final case-control sample of 142 mutation negative Lynch syndrome patients and 298 controls. The mutation analysis failed to reveal any rare disease-causing mutations. No association was found at the single-marker or haplotypic level for any common disease-modifying variant. The present results suggest that neither rare nor common genetic variants in ESR1, ESR2, MAX, PCNA, or KAT2A contribute to the development of Lynch syndrome.
Published online: 16 November 2011
The Dutch Cancer Genetics Group is represented by: Dr. A. Wagner, Dr. R. Sijmons, Dr. C. Aalfs, Dr. I. Kluijt, Dr. N. Hoogerbrugge, Dr. E. Gomez Garcia, Dr. F. Menko, Dr. T. Letteboer and Dr. F. Hes
Gesehen am 22.11.2018